Developing English-Speaking Materials for Broadcasting Students by Applying Project-Based Learning - annisa, maghfirah; Lubis, Nazriani (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2024)
Project-based Learning is the most appropriate teaching method suggested in Curriculum 2013. It consistsed of effective methods and integrated processes that assist vocational school students in overcome their English-learning difficulties. The problems in SMK SWASTA Dwi Tunggal 1 are English-speaking Materials for Broadcasting students are not specific, not integrated with Project-based Learning completely. The objective of the research is To increase the students English speaking skill. The subjects of the research consisted of 16 students. This research was categorized as research and development. It was undertaken to develop English-Speaking material for Broadcasting Major. In this research, the design of research that has been applied is ADDIE (Analysis, Design, Development, Implementation, Evaluation). the result of computation in N-Gain test, the average was 0.731, that means normal index criteria of N-Gain are accepted. Because it was higher than 0.7. So, the researcher concluded that developing English speaking materials by implementing project-based learning for broadcasting students is effective. It can be seen from the result of the means improvement between pre-test and post-test in class X from broadcasting major in SMK Dwi Tunggal. the mean of pre-test was 59.6 and the mean post-test was 89. Because of the pre-test was higher than post-test, so the model that applied in class X in developing English speaking materials is a good model and affect students’ speaking skill.